2015
DOI: 10.17554/j.issn.2313-5611.2015.01.28
|View full text |Cite
|
Sign up to set email alerts
|

Speech Rehabilitation in Parkinson’s Disease

Abstract: The purpose of this review was to evaluate the different speech therapy approaches for persons with Parkinson's Disease (PD). Treatment methods reviewed include speech therapy (LSVT), pharmacological therapy and deep brain stimulation (DBS). Recent research data show that speech therapy has proven to be the most effective therapeutic strategy for improving voice and speech function. Pharmacotherapy or DBS methods not combined with speech therapy do not appear to significantly improve voice and speech function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The outcomes showed that the use of an exercise sequence that included overarticulation technique can improve communication and that this improvement is still present for at least 15 minutes. Data from the literature shows that the effects on the speech (24) of PD patients with DBS are particular; some patients get worse while others do not. However, in most cases the treatment does not change the speech pattern (25) , like other pharmacological treatments (24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes showed that the use of an exercise sequence that included overarticulation technique can improve communication and that this improvement is still present for at least 15 minutes. Data from the literature shows that the effects on the speech (24) of PD patients with DBS are particular; some patients get worse while others do not. However, in most cases the treatment does not change the speech pattern (25) , like other pharmacological treatments (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the rehabilitation using vocal exercises, the LSVT is the treatment most common and used worldwide, despite the stage of the PD (24) . Although with different exercises and different duration of the intervention, the vocal training in the LSVT is intense, with daily session that happens during one month, the maintenance of the results after the LSVT intervention has been proven (9) and it can be maintained for at least two to three years (24) . However, no studies that analyzed the effects of vocal techniques for patients with PD treated with DB were found, once the DBS is considered to be a treatment (24) .…”
Section: Discussionmentioning
confidence: 99%